A Case of Aortopulmonary Window: Asymptomatic until the First Pregnancy - Murat Kose; Serra Ucar; Samim Emet; Timur Selcuk Akpinar; Kıvanc Yalin (Case Reports in Cardiology)
The aortopulmonary window (APW) is an abnormal communication between the ascending aorta and the pulmonary trunk in the presence of two separate semilunar valves. It is a rare congenital malformation which represents 0.1% of all congenital cardiac diseases. Herein, we report a very rare case of 27-year-old patient with unrepaired APW causing Eisenmenger syndrome and pulmonary hypertension who was asymptomatic until her first pregnancy. The median survival of uncorrected APW is 33 years. Aortopulmonary window is a very rare congenital anomaly. To our knowledge, asymptomatic adult case has not been reported until now. APW should be considered in the differential diagnosis of the severe pulmonary hypertension also in adult patients.